"fine-Sgraffito Ware," "aegean Ware" From Anaia: an Analytical Approach - Budak Ünaler, Meral; Akkurt, Sedat (Izmir Institute of Technology, 2013)
Excavation in Byzantine castle, known as Kuşadası Kadıkalesi, Anaia provided ceramic finds which dates back to mid 12th and 13th century of Mid Byzantine period. These finds were produced as serial products. In first part of the thesis 47 samples with four different decoration repertoire; Fine Sgraffito, Incised-Sgraffito, Incised and Champlevé, were analyzed by Scanning Electron Microscope (SEM-EDX), X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) methods, in order to identify the three distinct layers in cross sections: body, slip and glaze layers. Body was largely composed of SiO2, Al2O3, CaO, Fe2O3, Na2O and K2O along with other less abundant elements. Slip had similar chemistry but with less Fe2O3. The glaze was composed mainly of lead oxide. Between the glaze and the slip some new well formed crystals of lead feldspar were found to precipitate in dimensions of roughly 10-50 m. Statistical analysis tools like Hierarchical Clustering Analysis (HCA) and Principal Component Analysis (PCA) were used to see if any groupings were possible between the samples collected. Dendrograms indicated that these ceramics were made of two different types of clay. In second part of the thesis, replicate samples of earthenware pottery were manufactured in the laboratory to mimic the formation of the glazed pottery. Similar microstructural features were identified. Another HCA study was done to compare the Anaia samples with the literature. Dendrograms obtained showed some similarity. However, it was not possible to strongly and conclusively say that the two sample groups were related.
Thesis (Doctoral)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2013
Includes bibliographical references (leaves: 155-164)
Text in English; Abstract: Turkish and English
xi, 164 leaves
Keywords: Pottery, Byzantine; Pottery--Analysis; Scanning electron microscopy in archaeology; X-ray spectroscopy in archaeology; Archaeology--Methodology